INTEGRASI EPISTEMOLOGI ABID AL-JABIRI DALAM PEMBELAJARAN PAI UNTUK MENGEMBANGKAN PEMIKIRAN KRITIS DI PERGURUAN TINGGI - Amin, Moh. Nasrul (Universitas Kiai Abdullah Faqih Gresik, 2025)
Abstract: The objective of this research is to explore the integration model of Abid Al-Jabiri's epistemology in Islamic Religious Education (PAI) learning to develop critical thinking at the university level. The research employs a library research method, utilizing primary data derived from Muhammad Abid Al-Jabiri's works related to the epistemologies of bayani, burhani, and irfani. Secondary data are drawn from journals and books discussing Muhammad Abid Al-Jabiri and their relevance to this research. Data analysis uses content analysis by selecting data that aligns with the core themes of the study. The findings indicate that the integration of Muhammad Abid Al-Jabiri's epistemology in PAI learning at universities can foster students' critical thinking through an integrative-holistic model. The learning stages include: Bayani Stage (Authentic Learning): This stage facilitates a foundational understanding of Islamic teachings through religious texts and evidences. Burhani Stage (Critical-Contextual Thinking): This stage emphasizes reasoning based on Islamic evidences analyzed through rational intellect, involving empirical data or social issues arising in the community. Irfani Stage (Spiritual-Emotional Learning): This stage prioritizes spiritual experiences as a source of knowledge. Through this integrative-holistic learning model, PAI instruction at universities can effectively enhance students’ critical thinking while deepening their comprehensive understanding of Islamic teachings.